Migration-resistant cable sheath material and preparation process thereof
By combining polyvinyl chloride powder, diisodecyl phthalate, mica powder-adipate polyester, flame retardant and antioxidant, the problems of migration resistance and flame retardancy of cable sheath materials in complex environments are solved, and the long-term stability and safety of the materials are improved.
Patent Information
- Application Number
- CN202511326080.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-17
- Publication Date
- 2025-12-02
AI Technical Summary
Existing cable sheath materials are prone to molecular chain breakage or oxidative degradation when exposed to sunlight, oxygen, and alternating high and low temperatures for extended periods. This leads to material hardening and cracking, and plasticizers and stabilizers are prone to migration, affecting flexibility and sealing performance and shortening cable lifespan.
By employing a combination of polyvinyl chloride powder, diisodecyl phthalate, mica powder-adipate polyester, flame retardant, and antioxidant, and through precise preparation and step-by-step addition processes, a synergistic effect is achieved, which enhances the material's migration resistance, flame retardancy, and flexibility, prevents the migration of small molecule additives, and ensures stable material performance.
It improves the migration resistance and flame retardant properties of cable sheath materials, extends the service life of cables, enhances the overall reliability and safety of materials, and adapts to application requirements in complex environments.
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer materials technology, specifically to a migration-resistant cable sheath material and its preparation process. Background Technology
[0002] Cable sheath is the outermost protective structure wrapped around a cable. Its main function is to protect the core components inside the cable, such as the conductor and insulation layer, from the influence of the external environment, ensuring that the cable can operate safely and stably in various scenarios. It has a wide range of applications in many fields such as power transmission, rail transportation, and building wiring.
[0003] In existing technologies, cable sheath materials lack sufficient weather resistance and aging resistance. Traditional materials (such as PVC and PE) are prone to molecular chain breakage or oxidative degradation when exposed to sunlight, oxygen, and alternating high and low temperatures for extended periods. This leads to material hardening, cracking, and loss of protection for the cable. Furthermore, small molecule additives such as plasticizers and stabilizers added to improve material performance tend to migrate from the material's interior to the surface during long-term use, or react with and be lost from the surrounding environment (such as moisture and grease). This migration of additives reduces material flexibility, causing sheath cracking, sealing failure, and severely shortening the cable's service life.
[0004] Based on this, the present invention provides a process for preparing a migration-resistant cable sheath material. Summary of the Invention
[0005] The purpose of this invention is to provide a migration-resistant cable sheath material and its preparation process. The cable sheath material prepared by this invention not only has good migration resistance and tensile strength, but also has a high oxygen index and excellent flame retardant properties.
[0006] To achieve the above objectives, the present invention provides the following technical solution: a migration-resistant cable sheath material, comprising the following raw materials in parts by weight: 50-70 parts polyvinyl chloride powder, 10-20 parts diisodecyl phthalate, 5-15 parts mica powder-adipate polyester, 3-8 parts flame retardant, and 1-3 parts antioxidant. The diisodecyl phthalate was prepared from isodecyl alcohol and phthalic anhydride; The mica powder-adipic acid polyester is prepared by surface-modified mica powder and adipic acid polyester.
[0007] Preferably, the preparation method of diisodecyl phthalate is as follows: isodecyl alcohol and phthalic anhydride are added to a reactor, cyclohexane is added as a dehydrating agent, nitrogen gas is introduced to purge air and maintain a slight positive pressure, the temperature is raised to 170-180℃ and maintained for 0.5h, then a non-acidic organometallic salt catalyst is added, the reaction is carried out for 5-6h, and the final temperature is controlled at 200-220℃ to obtain crude diisodecyl phthalate; it is then put into a vacuum filtration device and filtered for 1-2 hours at a pressure of (-0.085)-(-0.095) MPa and a temperature of 170-180℃. h, add 4-5% sodium hydroxide aqueous solution for alkaline washing, maintain the temperature at 80-85℃, stir for 0.5h and then stop stirring and separate the aqueous solution. Repeat alkaline washing 3 times. After alkaline washing, wash with water, each time adding 25-35% of the weight of the crude product, at a temperature of 80-85℃, stir and wash with water for 1h and then stop stirring and separate the aqueous layer. Wash with water multiple times until the pH of the aqueous layer is 7-8. Strip the crude product after washing with water at 160-170℃ for 1h, then add activated carbon and decolorize in a decolorizing device at 90-100℃ for 1h to complete the preparation of diisodecyl phthalate.
[0008] Preferably, the preparation method of the adipic acid-based polyester is as follows: adipic acid and ethylene glycol are added to a reaction vessel at a molar ratio of 1:(1.1-1.3), and 0.1-0.3% of tetrabutyl titanate catalyst by total mass is added. Under nitrogen protection, the reaction is first carried out at 160-180℃ for 2-3 hours, and then polycondensed at 220-240℃ and pressure ≤5kPa for 4-6 hours to obtain an adipic acid-based polyester with a number average molecular weight of 8000-12000.
[0009] Preferably, the preparation method of the mica powder-adipate polyester is as follows: mica powder is added to a silane coupling agent ethanol solution with a mass fraction of 5-10%, the mass ratio of mica powder to solution is 1:(5-8), and stirred at a temperature of 50-70℃ and a rotation speed of 200-300 r / min for 1-2 h. After filtration, it is dried at 80-100℃ for 2-3 h to obtain surface-modified mica powder. The modified mica powder and adipate polyester are added to a reaction vessel at a mass ratio of (1-3):(5-8), and reacted at a temperature of 180-220℃ and a pressure of 0.1-0.3 MPa under nitrogen protection for 4-6 h. After cooling to room temperature, it is pulverized to complete the preparation of mica powder-adipate polyester.
[0010] Preferably, the preparation method of the polymer non-migrating polyester plasticizer composite system is as follows: diisodecyl phthalate and mica powder-adipate polyester are added to a mixing tank at a mass ratio of (2-4):(1-3), stirred at a temperature of 60-80℃ and a rotation speed of 300-500 r / min for 30-60 min, and then transferred to an ultrasonic disperser and ultrasonically treated at a power of 200-400W for 20-40 min to form a hydrogen bonded composite. The interlayer spacing of mica powder is detected by X-ray diffraction, and the interlayer spacing is controlled to be 1.2-1.8 nm by adjusting the ultrasonic power to obtain the polymer non-migrating polyester plasticizer composite system.
[0011] Preferably, the antioxidant is antioxidant 1076, antioxidant 1010, or a mixture of the two in a mass ratio of 1:1, with a purity ≥99%, and the flame retardant is one of magnesium hydroxide or aluminum hydroxide.
[0012] A process for preparing a migration-resistant cable sheath material includes the following steps: pretreating a flame retardant; employing a step-by-step addition process, first adding PVC powder and a portion of a polymer non-migratory polyester plasticizer composite system to a high-speed mixer for premixing, then adding the remaining polymer non-migratory polyester plasticizer composite system and the pretreated flame retardant to the premix for blending to obtain a mixture; feeding the mixture into a twin-screw extruder, setting appropriate parameters, and after melt extrusion, water cooling and pelletizing to obtain migration-resistant cable sheath material granules; and extruding the granules into cable sheaths using an extrusion molding process, with an extrusion temperature of 170-190℃ and a traction speed of 5-10 m / min.
[0013] Preferably, the pretreatment method of the flame retardant is as follows: magnesium hydroxide or aluminum hydroxide is added to a stearic acid ethanol solution with a mass fraction of 3-5%, the mass ratio of flame retardant to solution is 1:(4-6), and the mixture is treated at a temperature of 70-90℃ and an ultrasonic power of 100-300W for 30-50 minutes. After filtration, the mixture is dried at 100-120℃ for 3-4 hours to obtain a surface-modified flame retardant with an average particle size controlled at 1-5μm.
[0014] Preferably, the stepwise addition process premixing method is as follows: PVC powder and 50-60% by weight of a high-molecular non-molecular polyester plasticizer composite system are added to a high-speed mixer and premixed for 10-15 minutes at a temperature of 90-110℃ and a rotation speed of 800-1200 r / min to obtain a premix; secondary blending: the remaining 40-50% by weight of the composite system and flame retardant are added to the premix and blended for 15-20 minutes at a temperature of 100-120℃ and a rotation speed of 600-900 r / min to obtain a mixed material.
[0015] Preferably, the twin-screw extruder has segmented temperature control, wherein the feeding section is 140-160℃, the melting section is 160-180℃, the homogenization section is 170-190℃, and the die head section is 160-180℃. The screw speed is 200-300 r / min, the vacuum degree is controlled at (-0.06)-(-0.08) MPa, the material residence time in the barrel is 3-5 min, and the screw length-to-diameter ratio of the twin-screw extruder is 36:1.
[0016] Compared with the prior art, the beneficial effects of the present invention are: 1. In this invention, polyvinyl chloride (PVC) serves as the base matrix, which synergistically interacts with diisodecyl phthalate (DID) and mica-adipate polyester. DID, through precise preparation, effectively enhances the material's flexibility and processing fluidity. Meanwhile, the mica-adipate polyester, through surface modification and specific composite processes, possesses a unique structure that constructs a physical barrier network within the material. The synergistic effect of these two components is twofold: firstly, DID optimizes processing performance, facilitating cable sheath molding; secondly, the barrier properties of the mica-adipate polyester inhibit the migration of small-molecule additives, ensuring stable performance during long-term use, extending the cable sheath's service life, and improving the overall reliability of the cable.
[0017] 2. The flame retardant and antioxidant of this invention exert synergistic advantages in the system. After pretreatment, the surface modification of the flame retardant improves its dispersibility and compatibility in polyvinyl chloride matrix, enabling it to exert its flame retardant effect more efficiently and delay the spread of combustion. The antioxidant (1076, 1010 or a mixture thereof), with its high purity, can capture free radicals generated during material processing and use, inhibiting oxidative degradation. The two work synergistically, with the flame retardant reducing the risk of combustion from the source and the antioxidant maintaining the chemical stability of the material, jointly ensuring the safety and durability of the cable sheath in complex environments (such as high temperature and high oxygen), and reducing cable failures caused by material deterioration.
[0018] 3. The stepwise addition process of this invention, in synergy with the preparation processes of each raw material, achieves a leap in material performance. In terms of raw material preparation, the refining of diisodecyl phthalate, the polycondensation of adipic acid polyester, and the construction of mica powder composites ensure the high quality of each component. The stepwise addition process, through precise control of the temperature and speed of premixing and blending, ensures the uniform dispersion of polyvinyl chloride, plasticizer composites, flame retardants, etc. This synergy makes the internal structure of the material more compact, which not only improves mechanical properties (such as tensile strength) but also optimizes migration resistance, flame retardancy, and other functions, allowing the cable sheath to exhibit excellent comprehensive performance in molding and use, and adapt to a variety of harsh application scenarios. Detailed Implementation
[0019] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0020] It should be noted that all raw materials used in the following experiments are commercially available.
[0021] Example 1: A migration-resistant cable sheath material, comprising the following raw materials in parts by weight: 50 parts polyvinyl chloride powder, 10 parts diisodecyl phthalate, 5 parts mica powder-adipate polyester, 3 parts flame retardant, and 1 part antioxidant. Diisodecyl phthalate is prepared from isodecyl alcohol and phthalic anhydride; Mica powder-adipic acid polyester is prepared by surface-modified mica powder and adipic acid polyester.
[0022] The preparation method of diisodecyl phthalate is as follows: isodecyl alcohol and phthalic anhydride are added to a reactor, cyclohexane is added as a dehydrating agent, nitrogen gas is introduced to purge air and maintain a slight positive pressure, the temperature is raised to 170℃ and maintained for 0.5 h, then a non-acidic organometallic salt catalyst (tetrabutyl titanate) is added, the reaction is carried out for 5 h, and the final temperature is controlled at 200℃ to obtain crude diisodecyl phthalate; it is then put into a vacuum filtration device and filtered for 1 h at a pressure of -0.085 MPa and a temperature of 170℃. Add 4% sodium hydroxide aqueous solution for alkaline washing, maintain the temperature at 80℃, stir and wash for 0.5h, then stop stirring and separate the aqueous solution. Repeat alkaline washing 3 times. After alkaline washing, wash with water, each time adding 25% of the weight of the crude product, at 80℃, stir and wash with water for 1h, then stop stirring and separate the aqueous layer. Wash with water multiple times until the pH of the aqueous layer is 7. Strip the crude product at 160℃ for 1h, then add activated carbon and decolorize in a decolorizing device at 90℃ for 1h to complete the preparation of diisodecyl phthalate.
[0023] The preparation method of adipic acid-based polyester is as follows: adipic acid and ethylene glycol are added to a reaction vessel at a molar ratio of 1:(1.1-1.3), and 0.1-0.3% of tetrabutyl titanate catalyst is added. Under nitrogen protection, the reaction is first carried out at 160-180℃ for 2-3 hours, and then polycondensed at 220-240℃ and pressure ≤5kPa for 4-6 hours to obtain adipic acid-based polyester with a number average molecular weight of 8000-12000.
[0024] The preparation method of adipic acid polyester is as follows: adipic acid and ethylene glycol are added to a reaction vessel at a molar ratio of 1:1.1, and 0.1% of tetrabutyl titanate catalyst is added. Under nitrogen protection, the reaction is first carried out at 160℃ for 2 hours, and then polycondensed at 220℃ and pressure ≤5kPa for 4 hours to obtain adipic acid polyester with a number average molecular weight of 8000.
[0025] The preparation method of mica powder-adipate polyester is as follows: Mica powder is added to a 5% (w / w) silane coupling agent ethanol solution at a mica powder to solution mass ratio of 1:5. The mixture is stirred at 50℃ and 200 r / min for 1 h, filtered, and dried at 80℃ for 2 h to obtain surface-modified mica powder. The modified mica powder and adipate polyester are added to a reaction vessel at a mass ratio of 1:5. The mixture is reacted at 180℃ and 0.1 MPa under nitrogen protection for 4 h. After cooling to room temperature, the mixture is pulverized to complete the preparation of mica powder-adipate polyester.
[0026] The preparation method of the polymer non-migrating polyester plasticizer composite system is as follows: Diisodecyl phthalate and mica powder-adipate polyester are added to a mixing tank at a mass ratio of 2:1 and stirred at 60℃ and 300 r / min for 30 min. Then, the mixture is transferred to an ultrasonic disperser and ultrasonically treated at 200W for 20 min to form a hydrogen bonded composite. The interlayer spacing of the mica powder is detected by X-ray diffraction. The interlayer spacing is controlled to be 1.2 nm by adjusting the ultrasonic power to obtain the polymer non-migrating polyester plasticizer composite system.
[0027] The antioxidant is antioxidant 1076 with a purity of ≥99%, and the flame retardant is either magnesium hydroxide or aluminum hydroxide.
[0028] A process for preparing a migration-resistant cable sheath material includes the following steps: pretreating a flame retardant; employing a step-by-step addition process, first adding PVC powder and a portion of a polymer non-migratory polyester plasticizer composite system to a high-speed mixer for premixing, then adding the remaining polymer non-migratory polyester plasticizer composite system and the pretreated flame retardant to the premix for blending to obtain a mixture; feeding the mixture into a twin-screw extruder, setting appropriate parameters, and after melt extrusion, water cooling and pelletizing to obtain migration-resistant cable sheath material granules; and extruding the granules into cable sheaths using an extrusion molding process at an extrusion temperature of 170℃ and a traction speed of 5m / min.
[0029] The pretreatment method for the flame retardant is as follows: magnesium hydroxide or aluminum hydroxide is added to a 3% stearic acid ethanol solution with a flame retardant to solution mass ratio of 1:4. The solution is treated at 70℃ and ultrasonic power of 100W for 30 minutes, filtered, and dried at 100℃ for 3 hours to obtain a surface-modified flame retardant with an average particle size controlled at 1μm.
[0030] The stepwise addition process premixing method is as follows: PVC powder and 50% by weight of high molecular weight non-migrating polyester plasticizer composite system are added to a high-speed mixer and premixed for 10 minutes at a temperature of 90℃ and a speed of 800 r / min to obtain a premixed material; secondary blending: the remaining 50% by weight of the composite system and flame retardant are added to the premixed material and blended for 15 minutes at a temperature of 100℃ and a speed of 600 r / min to obtain a mixed material.
[0031] The twin-screw extruder features segmented temperature control: 140°C for the feeding section, 160°C for the melting section, 170°C for the homogenizing section, and 160°C for the die head section. The screw speed is 200 r / min, the vacuum degree is controlled at -0.06 MPa, the material residence time in the barrel is 3 min, and the screw length-to-diameter ratio of the twin-screw extruder is 36:1.
[0032] Example 2: A migration-resistant cable sheath material, comprising the following raw materials in parts by weight: 60 parts polyvinyl chloride powder, 15 parts diisodecyl phthalate, 10 parts mica powder-adipate polyester, 5 parts flame retardant, and 2 parts antioxidant. Diisodecyl phthalate is prepared from isodecyl alcohol and phthalic anhydride; Mica powder-adipic acid polyester is prepared by surface-modified mica powder and adipic acid polyester.
[0033] The preparation method of diisodecyl phthalate is as follows: isodecyl alcohol and phthalic anhydride are added to a reactor, cyclohexane is added as a dehydrating agent, nitrogen gas is introduced to purge air and maintain a slight positive pressure, the temperature is raised to 175℃ and maintained for 0.5 h, then a non-acidic organometallic salt catalyst (tetrabutyl titanate) is added, the reaction is carried out for 5.5 h, and the final temperature is controlled at 210℃ to obtain crude diisodecyl phthalate; it is then put into a vacuum filtration device and filtered for 1.5 h at a pressure of -0.090 MPa and a temperature of 175℃. Add a 4.5% sodium hydroxide aqueous solution for alkaline washing, maintain the temperature at 82℃, stir and wash for 0.5h, then stop stirring and separate the aqueous solution. Repeat the alkaline washing 3 times. After the alkaline washing is completed, wash with water, each time adding 30% of the weight of the crude product, at a temperature of 82℃, stir and wash with water for 1h, then stop stirring and separate the aqueous layer. Wash with water multiple times until the pH of the aqueous layer is 7.5. Strip the crude product after washing at 165℃ for 1h, then add activated carbon and decolorize in a decolorizing device at 95℃ for 1h to complete the preparation of diisodecyl phthalate.
[0034] The preparation method of adipic acid polyester is as follows: adipic acid and ethylene glycol are added to a reaction vessel at a molar ratio of 1:1.2, and 0.2% of tetrabutyl titanate catalyst is added. Under nitrogen protection, the reaction is first carried out at 170℃ for 2.5h, and then polycondensed at 230℃ and pressure ≤5kPa for 5h to obtain adipic acid polyester with a number average molecular weight of 10000.
[0035] The preparation method of mica powder-adipate polyester is as follows: Mica powder is added to a 7% (w / w) silane coupling agent ethanol solution at a mica powder to solution mass ratio of 1:6. The mixture is stirred at 60℃ and 250 r / min for 1.5 h, filtered, and dried at 90℃ for 2.5 h to obtain surface-modified mica powder. The modified mica powder and adipate polyester are added to a reaction vessel at a mass ratio of 2:6. The mixture is reacted at 200℃ and 0.2 MPa under nitrogen protection for 5 h. After cooling to room temperature, the mixture is pulverized to complete the preparation of mica powder-adipate polyester.
[0036] The preparation method of the polymer non-migrating polyester plasticizer composite system is as follows: Diisodecyl phthalate and mica powder-adipate polyester are added to a mixing tank at a mass ratio of 3:2. The mixture is stirred at 70℃ and 400 r / min for 45 min. Then, it is transferred to an ultrasonic disperser and ultrasonically treated at 300W for 30 min to form a hydrogen bonded composite. The interlayer spacing of the mica powder is detected by X-ray diffraction. The interlayer spacing is controlled to 1.5 nm by adjusting the ultrasonic power to obtain the polymer non-migrating polyester plasticizer composite system.
[0037] The antioxidant is antioxidant 1010 with a purity of ≥99%, and the flame retardant is either magnesium hydroxide or aluminum hydroxide.
[0038] A process for preparing a migration-resistant cable sheath material includes the following steps: pretreating a flame retardant; employing a step-by-step addition process, first adding PVC powder and a portion of a polymer non-migratory polyester plasticizer composite system to a high-speed mixer for premixing, then adding the remaining polymer non-migratory polyester plasticizer composite system and the pretreated flame retardant to the premix for blending to obtain a mixture; feeding the mixture into a twin-screw extruder, setting appropriate parameters, and after melt extrusion, water cooling and pelletizing to obtain migration-resistant cable sheath material granules; and extruding the granules into cable sheaths using an extrusion molding process at an extrusion temperature of 180℃ and a traction speed of 7m / min.
[0039] The pretreatment method for the flame retardant is as follows: magnesium hydroxide or aluminum hydroxide is added to a 4% stearic acid ethanol solution with a flame retardant to solution mass ratio of 1:5. The solution is treated at 80℃ and ultrasonic power of 200W for 40 minutes, filtered, and dried at 110℃ for 3.5 hours to obtain a surface-modified flame retardant with an average particle size controlled at 3μm.
[0040] The stepwise addition process premixing method is as follows: PVC powder and 55% by weight of high molecular weight non-migrating polyester plasticizer composite system are added to a high-speed mixer and premixed for 12 minutes at a temperature of 100℃ and a speed of 1000 r / min to obtain a premixed material; secondary blending: the remaining 45% by weight of the composite system and flame retardant are added to the premixed material and blended for 17 minutes at a temperature of 110℃ and a speed of 750 r / min to obtain a mixed material.
[0041] The twin-screw extruder features segmented temperature control: 150°C for the feeding section, 170°C for the melting section, 180°C for the homogenizing section, and 170°C for the die head section. The screw speed is 250 r / min, the vacuum degree is controlled at -0.07 MPa, the material residence time in the barrel is 4 min, and the screw length-to-diameter ratio of the twin-screw extruder is 36:1.
[0042] Example 3: A migration-resistant cable sheath material, comprising the following raw materials in parts by weight: 70 parts polyvinyl chloride powder, 20 parts diisodecyl phthalate, 15 parts mica powder-adipate polyester, 8 parts flame retardant, and 3 parts antioxidant. Diisodecyl phthalate is prepared from isodecyl alcohol and phthalic anhydride; Mica powder-adipic acid polyester is prepared by surface-modified mica powder and adipic acid polyester.
[0043] The preparation method of diisodecyl phthalate is as follows: isodecyl alcohol and phthalic anhydride are added to a reactor, cyclohexane is added as a dehydrating agent, nitrogen gas is introduced to purge air and maintain a slight positive pressure, the temperature is raised to 180℃ and maintained for 0.5 h, then a non-acidic organometallic salt catalyst (tetrabutyl titanate) is added, the reaction is carried out for 6 h, and the final temperature is controlled at 220℃ to obtain crude diisodecyl phthalate; it is then put into a vacuum filtration device and filtered for 2 h at a pressure of -0.095 MPa and a temperature of 180℃. Alkaline washing with a 5% sodium hydroxide aqueous solution was performed while maintaining the temperature at 85℃. After stirring and washing for 0.5 hours, stirring was stopped and the aqueous solution was separated. This alkaline washing was repeated 3 times. After the alkaline washing was completed, water was washed, with the amount of water added each time being 35% of the weight of the crude product. The temperature was 85℃, and the water was washed for 1 hour while stirring. After stopping the stirring, the aqueous layer was separated. This water washing was repeated multiple times until the pH of the aqueous layer was 8. The crude product after water washing was stripped at 170℃ for 1 hour, and then activated carbon was added and decolorized in a decolorizing device at 100℃ for 1 hour to complete the preparation of diisodecyl phthalate.
[0044] The preparation method of adipic acid polyester is as follows: adipic acid and ethylene glycol are added to a reaction vessel at a molar ratio of 1:1.3, and 0.3% of tetrabutyl titanate catalyst is added. Under nitrogen protection, the reaction is first carried out at 180℃ for 3 hours, and then polycondensed at 240℃ and pressure ≤5kPa for 6 hours to obtain adipic acid polyester with a number average molecular weight of 12000.
[0045] The preparation method of mica powder-adipate polyester is as follows: Mica powder is added to a 10% (w / w) silane coupling agent ethanol solution at a mass ratio of 1:8. The mixture is stirred at 70℃ and 300 r / min for 2 h, filtered, and dried at 100℃ for 3 h to obtain surface-modified mica powder. The modified mica powder and adipate polyester are added to a reaction vessel at a mass ratio of 3:8. The mixture is reacted at 220℃ and 0.3 MPa under nitrogen protection for 6 h. After cooling to room temperature, the mixture is pulverized to complete the preparation of mica powder-adipate polyester.
[0046] The preparation method of the polymer non-migrating polyester plasticizer composite system is as follows: Diisodecyl phthalate and mica powder-adipate polyester are added to a mixing tank at a mass ratio of 4:3. The mixture is stirred at 80℃ and 500r / min for 60min. Then, it is transferred to an ultrasonic disperser and ultrasonically treated at 400W for 40min to form a hydrogen bonded composite. The interlayer spacing of the mica powder is detected by X-ray diffraction. The interlayer spacing is controlled to 1.8nm by adjusting the ultrasonic power to obtain the polymer non-migrating polyester plasticizer composite system.
[0047] The antioxidant is a mixture of antioxidant 1076 and antioxidant 1010 in a mass ratio of 1:1, with a purity of ≥99%, and the flame retardant is either magnesium hydroxide or aluminum hydroxide.
[0048] A process for preparing a migration-resistant cable sheath material includes the following steps: pretreating a flame retardant; employing a step-by-step addition process, first adding PVC powder and a portion of a polymer non-migratory polyester plasticizer composite system to a high-speed mixer for premixing, then adding the remaining polymer non-migratory polyester plasticizer composite system and the pretreated flame retardant to the premix for blending to obtain a mixture; feeding the mixture into a twin-screw extruder, setting appropriate parameters, and after melt extrusion, water cooling and pelletizing to obtain migration-resistant cable sheath material granules; and extruding the granules into cable sheaths using an extrusion molding process at an extrusion temperature of 190℃ and a traction speed of 10m / min.
[0049] The pretreatment method for flame retardant is as follows: magnesium hydroxide or aluminum hydroxide is added to a 5% stearic acid ethanol solution with a flame retardant to solution mass ratio of 1:6. The solution is treated at 90℃ and ultrasonic power of 300W for 50 min, filtered, and dried at 120℃ for 4 h to obtain a surface-modified flame retardant with an average particle size controlled at 5 μm.
[0050] The stepwise addition process premixing method is as follows: PVC powder and 60% by weight of high molecular weight non-migration polyester plasticizer composite system are added to a high-speed mixer and premixed for 15 minutes at a temperature of 110℃ and a speed of 1200 r / min to obtain a premixed material; secondary blending: the remaining 40% by weight of the composite system and flame retardant are added to the premixed material and blended for 20 minutes at a temperature of 120℃ and a speed of 900 r / min to obtain a mixed material.
[0051] The twin-screw extruder features segmented temperature control: 160°C for the feeding section, 180°C for the melting section, 190°C for the homogenizing section, and 180°C for the die head section. The screw speed is 300 r / min, the vacuum degree is controlled at -0.08 MPa, the material residence time in the barrel is 5 min, and the screw length-to-diameter ratio of the twin-screw extruder is 36:1.
[0052] Comparative Example 1: The difference between this comparative example and Example 1 is that no mica powder-adipic acid polyester is added in this comparative example.
[0053] Comparative Example 2: The difference between this comparative example and Example 1 is that the flame retardant in this comparative example was not pretreated.
[0054] Comparative Example 3 differs from Example 1 in that the mica powder interlayer spacing was not controlled by ultrasound in the preparation of the polymer non-migration polyester plasticizer composite system in this comparative example.
[0055] Comparative Example 4: The difference between this comparative example and Example 1 is that this comparative example does not use a step-by-step addition process.
[0056] Performance testing: Performance tests were conducted on the products prepared in Examples 1, 2, 3, 1, 2, 3, and 4. Migration resistance test: Wipe the sample surface with anhydrous ethanol to remove oil and impurities, then dry in a vacuum drying oven at 60℃ for 2 hours. After cooling to room temperature, weigh the sample, then place it in a clean glass petri dish, open it in a constant temperature oven, set the temperature to 80℃ for 72 hours. After the predetermined time, remove the sample, cool it to room temperature in a desiccator, weigh it immediately, and finally calculate the migration resistance. Refer to the test standard: GB31604.8-2016. Tensile strength test: Prepare a Type I dumbbell-shaped specimen (115mm long, 50mm gauge length, 2mm thickness) from the finished cable sheath material or extruded strip according to the requirements. Clamp the specimen on the electronic universal testing machine fixture, ensuring that the longitudinal axis of the specimen is aligned with the tensile direction. The fixture spacing is 50mm. Tensile test is performed at a speed of (50±5)mm / min. Record the maximum load at which the specimen breaks. If the specimen breaks outside the gauge length, the data is invalid and the test must be repeated. Test standard: GB / T1633-2000; Oxygen index test: Pass Preliminary testing determines the range of the oxygen index (e.g., if a sample burns for <3 minutes at 29% oxygen concentration and ≥3 minutes at 30% oxygen concentration, the range is 29%-30%). Within this range, the oxygen concentration is adjusted in increments of 0.5%. One sample is tested at each concentration until two adjacent concentrations (e.g., 29.5% and 30.0%) are found where the sample burns for <3 minutes at one concentration and ≥3 minutes at the other. The oxygen index is then calculated. The test is based on GB / T2406.2-2009.
[0057] The obtained test data is recorded in the table below: Testing items Migration resistance (%) Tensile strength (MPa) Oxygen index (%) Example 1 0.3 21.5 31.0 Example 2 0.2 23.8 32.5 Example 3 0.15 25.2 34.0 Comparative Example 1 3.5 14.2 30.8 Comparative Example 2 1.2 19.8 31.2 Comparative Example 3 0.4 18.3 27.5 Comparative Example 4 0.6 17.5 30.5 By comparing and analyzing the relevant data in the table, it can be seen that the cable sheath material prepared by the migration-resistant cable sheath material preparation process of this invention not only has good migration resistance and tensile strength, but also a high oxygen index and excellent flame retardant properties. This indicates that the migration-resistant cable sheath material preparation process provided by this invention has a broader market prospect and is more suitable for widespread application.
[0058] In the description of this specification, references to terms such as "an embodiment," "example," and "specific example" indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0059] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to the specific implementations described. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.
Claims
1. A migration-resistant cable sheath material, characterized in that: It includes the following raw materials by weight: 50-70 parts polyvinyl chloride powder, 10-20 parts diisodecyl phthalate, 5-15 parts mica powder-adipic acid polyester, 3-8 parts flame retardant, and 1-3 parts antioxidant. The diisodecyl phthalate was prepared from isodecyl alcohol and phthalic anhydride; The mica powder-adipic acid polyester is prepared by surface-modified mica powder and adipic acid polyester.
2. The migration-resistant cable sheath material according to claim 1, characterized in that, The preparation method of diisodecyl phthalate is as follows: isodecyl alcohol and phthalic anhydride are added to a reactor, cyclohexane is added as a dehydrating agent, nitrogen gas is introduced to purge air and maintain a slight positive pressure, the temperature is raised to 170-180℃ and maintained for 0.5h, then a non-acidic organometallic salt catalyst is added, the reaction is carried out for 5-6h, and the final temperature is controlled at 200-220℃ to obtain crude diisodecyl phthalate; it is then put into a vacuum filtration device and filtered for 1-2h at a pressure of (-0.085)-(-0.095) MPa and a temperature of 170-180℃. Add a 4-5% sodium hydroxide aqueous solution for alkaline washing, maintain the temperature at 80-85℃, stir and wash for 0.5h, then stop stirring and separate the aqueous solution. Repeat the alkaline washing 3 times. After the alkaline washing is completed, wash with water, each time adding 25-35% of the weight of the crude product, at a temperature of 80-85℃, stir and wash with water for 1h, then stop stirring and separate the aqueous layer. Wash with water multiple times until the pH of the aqueous layer is 7-8. Strip the crude product after washing with water at 160-170℃ for 1h, then add activated carbon and decolorize in a decolorizing device at 90-100℃ for 1h to complete the preparation of diisodecyl phthalate.
3. The migration-resistant cable sheath material according to claim 1, characterized in that, The preparation method of the adipic acid-based polyester is as follows: adipic acid and ethylene glycol are added to a reaction vessel at a molar ratio of 1:(1.1-1.3), and 0.1-0.3% of tetrabutyl titanate catalyst is added. Under nitrogen protection, the reaction is first carried out at 160-180℃ for 2-3 hours, and then polycondensed at 220-240℃ and pressure ≤5kPa for 4-6 hours to obtain an adipic acid-based polyester with a number average molecular weight of 8000-12000.
4. The migration-resistant cable sheath material according to claim 1, characterized in that, The preparation method of the mica powder-adipate polyester is as follows: add mica powder to a silane coupling agent ethanol solution with a mass fraction of 5-10% and a mica powder to solution mass ratio of 1:(5-8). Stir at 50-70℃ and 200-300 r / min for 1-2 h. After filtration, dry at 80-100℃ for 2-3 h to obtain surface-modified mica powder. Add the modified mica powder and adipate polyester to a reaction vessel at a mass ratio of (1-3):(5-8). Under nitrogen protection, react at 180-220℃ and 0.1-0.3 MPa for 4-6 h. After cooling to room temperature, pulverize to complete the preparation of mica powder-adipate polyester.
5. The migration-resistant cable sheath material according to claim 1, characterized in that, The preparation method of the polymer non-migrating polyester plasticizer composite system is as follows: Diisodecyl phthalate and mica powder-adipate polyester are added to a mixing tank at a mass ratio of (2-4):(1-3), and stirred for 30-60 min at a temperature of 60-80℃ and a rotation speed of 300-500 r / min. Then, the mixture is transferred to an ultrasonic disperser and ultrasonically treated for 20-40 min at a power of 200-400W to form a hydrogen bonded composite. The interlayer spacing of the mica powder is detected by X-ray diffraction, and the interlayer spacing is controlled to be 1.2-1.8 nm by adjusting the ultrasonic power to obtain the polymer non-migrating polyester plasticizer composite system.
6. The migration-resistant cable sheath material according to claim 1, characterized in that: The antioxidant is antioxidant 1076, antioxidant 1010, or a mixture of the two in a mass ratio of 1:1, with a purity ≥99%, and the flame retardant is one of magnesium hydroxide or aluminum hydroxide.
7. A process for preparing a migration-resistant cable sheath material, comprising the migration-resistant cable sheath material according to any one of claims 1-6, characterized in that, Includes the following steps: The flame retardant is pretreated; a step-by-step addition process is adopted, firstly, PVC powder and part of the polymer non-migratory polyester plasticizer composite system are added to a high-speed mixer for premixing, then the remaining polymer non-migratory polyester plasticizer composite system and the pretreated flame retardant are added to the premix for blending to obtain a mixture; the mixture is fed into a twin-screw extruder, the corresponding parameters are set, and after melt extrusion, it is water-cooled and pelletized to obtain migration-resistant cable sheath material granules; the granules are extruded into cable sheaths, with an extrusion temperature of 170-190℃ and a traction speed of 5-10m / min.
8. The preparation process of a migration-resistant cable sheath material according to claim 7, characterized in that, The pretreatment method for the flame retardant is as follows: magnesium hydroxide or aluminum hydroxide is added to a stearic acid ethanol solution with a mass fraction of 3-5%, and the mass ratio of flame retardant to solution is 1:(4-6). The solution is treated at a temperature of 70-90℃ and an ultrasonic power of 100-300W for 30-50 minutes. After filtration, the solution is dried at 100-120℃ for 3-4 hours to obtain a surface-modified flame retardant with an average particle size controlled at 1-5μm.
9. The preparation process of a migration-resistant cable sheath material according to claim 7, characterized in that, The stepwise addition process premixing method is as follows: PVC powder and 50-60% by weight of high molecular weight non-migrating polyester plasticizer composite system are added to a high-speed mixer and premixed for 10-15 minutes at a temperature of 90-110℃ and a speed of 800-1200 r / min to obtain a premix; secondary blending: the remaining 40-50% by weight of the composite system and flame retardant are added to the premix and blended for 15-20 minutes at a temperature of 100-120℃ and a speed of 600-900 r / min to obtain a mixed material.
10. The preparation process of a migration-resistant cable sheath material according to claim 7, characterized in that: The twin-screw extruder features segmented temperature control, with the feeding section at 140-160℃, the melting section at 160-180℃, the homogenization section at 170-190℃, and the die head section at 160-180℃. The screw speed is 200-300 r / min, the vacuum degree is controlled at (-0.06)-(-0.08) MPa, and the material residence time in the barrel is 3-5 min. The length-to-diameter ratio of the screw in the twin-screw extruder is 36:1.